The importance of temperature and lipid accumulation for initiation and duration of Calanus hyperboreus spawning. (14th February 2020) - Schultz, Mads; Nielsen, Torkel Gissel; Møller, Eva Friis
Abstract: Large, lipid-storing copepods play a central role in marine Arctic ecosystems. Knowledge of the mechanisms that control their oogenesis is important for understanding their phenology and population dynamics. We investigated the impact of female lipid content on the timing and cumulative egg production (EP) of Calanus hyperboreus at 0, 3 and 6°C. The lipid content of females in early autumn was a good predictor of their EP potential. However, we saw no indication of a threshold in lipid content for initiation of spawning. Higher temperature resulted in 17 and 24 days earlier spawning at 3 and 6°C compared with 0°C, and the mean spawning duration was 8 and 30 days shorter, respectively. This illustrates that temperature affects the phenology of C. hyperboreus . When EP began, lipid metabolism increased 2–4 times. The females allocated 1.3 μg lipid per egg independent of temperature. However, the basic metabolism increased with increasing temperature; consequently, a smaller fraction of lipid was allocated for EP when the temperature increased.